2011
DOI: 10.1152/ajpheart.00831.2010
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 1 contributes to diminished coronary arteriolar dilation in patients with diabetes

Abstract: , via competing with nitric oxide (NO) synthase for the substrate L-arginine, may interfere with NO-mediated vascular responses. We tested the hypothesis that arginase 1 contributes to coronary vasomotor dysfunction in patients with diabetes mellitus (DM). Coronary arterioles were dissected from the right atrial appendages of 41 consecutive patients with or without DM (the 2 groups suffered from similar comorbidities), and agonist-induced changes in diameter were measured with videomicroscopy. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 41 publications
4
76
0
Order By: Relevance
“…12 Of further importance is the observation that arginase I is upregulated in coronary arterioles of patients with type 2 diabetes mellitus, contributing to a reduced NO production in vitro. 13 However, no previous study has evaluated the functional importance of arginase activity for endothelial function in patients with atherosclerosis and type 2 diabetes mellitus in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Of further importance is the observation that arginase I is upregulated in coronary arterioles of patients with type 2 diabetes mellitus, contributing to a reduced NO production in vitro. 13 However, no previous study has evaluated the functional importance of arginase activity for endothelial function in patients with atherosclerosis and type 2 diabetes mellitus in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent study showing that arginase I is upregulated in coronary arterioles of patients with type 2 diabetes mellitus, contributing to a reduced NO production in vitro. 13 However, whether arginase activity contributes to endothelial dysfunction in patients with CAD and diabetes mellitus in vivo is unknown. Thus, the main objective of the current study was to test the hypothesis that arginase contributes to the occurrence of endothelial dysfunction and that arginase blockade improves endothelial function in patients with CAD and type 2 diabetes mellitus.…”
Section: Clinical Perspective On P 2950mentioning
confidence: 99%
“…We (25) have also shown that STZ-induced diabetesinduced impairment of coronary vasorelaxation to ACh in rats was correlated with increases in ROS, arginase activity, and AI expression in the aorta. Additionally, a recent study (2) of diabetic human coronary arterioles demonstrated the involvement of upregulated AI in reduced NO production and vasodilation. Together, these results suggest that the involvement of arginase isoforms in vascular dysfunction varies depending on the model and disease condition.…”
Section: Vascular Functionmentioning
confidence: 97%
“…24 Moreover, coronary endothelial function is disrupted in type 2 diabetic patients and rodents. 27,28 The vascular redox status greatly contributes to endothelial homeostasis by modulating the function of TRP channels. 29 Mitochondrial ROS play an important role in the progression of coronary atherosclerosis and subsequent myocardial ischemic injury.…”
Section: Impairment Of Protective Targets Increases Mitochondrial Rosmentioning
confidence: 99%